Bladder cancer and occupation: a case-control study in northern Italy. Issue 1 (January 1996) - Porru, S; Aulenti, V; Donato, F; Boffetta, P; Fazioli, R; Cosciani Cunico, S; Alessio, L
Abstract : OBJECTIVES–A hospital based case-control study was conducted between 1992 and 1993 in the province of Brescia, a highly industrialised area in northern Italy, to evaluate occupational risk factors of bladder cancer. METHODS–The study evaluated 355 histologically confirmed cases of bladder cancer (275 men, 80 women) and 579 controls affected by urological non-neoplastic diseases (397 men, 182 women). Lifetime occupational history, smoking and drinking habits, and sociodemographic characteristics were recorded by means of a structured questionnaire. Odds ratios (ORs) were computed with adjustment for age, smoking, alcohol and coffee consumption, education, and place of residence. RESULTS–A significant (P < 0.05) increase of risk of bladder cancer were found in men for labourers in the construction industry (OR 2.1, 95% confidence interval (95% CI) 1.1-3.9) and for recreational and cultural services (OR 5.0, 95% CI 1.3-18.9). Increased risks, although not significant, were found for various other occupations and industries such as machinery mechanics, metal processers and polishers, blacksmiths, gunsmiths, painters; for transport workers, an increased risk with increasing duration of employment was found. CONCLUSIONS–Occupational exposures seem to contribute to bladder cancer risk in the area under study.